Addition of Lenalidomide to R-CHOP Improves Outcomes in Newly Diagnosed Diffuse Large B-Cell Lymphoma in a Randomized Phase II US Intergroup Study ECOG-ACRIN E1412. Issue 12 (20th April 2021) - Nowakowski, Grzegorz S.; Hong, Fangxin; Scott, David W.; Macon, William R.; King, Rebecca L.; Habermann, Thomas M.; Wagner-Johnston, Nina; Casulo, Carla; Wade, James L.; Nagargoje, Gauri G.; Reynolds, C. M.; Cohen, Jonathon B.; et al.
Abstract : PURPOSE: Lenalidomide combined with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) (R2CHOP) in untreated diffuse large B-cell lymphoma (DLBCL) has shown promising activity, particularly in the activated B-cell–like (ABC) subtype. Eastern Cooperative Oncology Group (ECOG)-ACRIN trial E1412 was a randomized phase II study comparing R2CHOP versus R-CHOP in untreated DLBCL. PATIENTS AND METHODS: Patients with newly diagnosed DLBCL, stage II bulky-IV disease, International Prognostic Index (IPI) ≥ 2, and ECOG performance status ≤ 2 were eligible and randomly assigned 1:1 to R2CHOP versus R-CHOP for six cycles. Tumors were analyzed using the NanoString Lymph2Cx for cell of origin. The primary end point was progression-free survival (PFS) in all patients with the co-primary end point of PFS in ABC-DLBCL. Secondary end points included overall response rate (ORR), complete response (CR) rate, and overall survival (OS). RESULTS: Three hundred forty-nine patients were enrolled; 280 patients (145 R2CHOP and 135 R-CHOP) were evaluable: 94 were ABC-DLBCL, 122 germinal center B-cell–like-DLBCL, 18 unclassifiable, and 46 unknowns. Baseline characteristics were well-balanced between arms, and the median age was 66 (range, 24-92); 70% of patients had stage IV disease; 34%, 43%, and 24% had IPI 2, 3, and 4 or 5, respectively. Myelosuppression was more common in the R2CHOP arm. The ORR and CR rate were 92% and 68% in R-CHOP and 97% ( P = .06) and 73% ( P = .43) in the R2CHOP arm, respectively. The median follow-up was 3.0 years; R2CHOP was associated with a 34% reduction in risk of progression or death versus R-CHOP (hazard ratio [HR], 0.66 95% CI, 0.43 to 1.01) and 3-year PFS of 73% versus 61%, one-sided P = .03, and an improvement in OS (83% and 75% at 3 years; HR, 0.67; one-sided P = .05). The PFS HR for R2CHOP was 0.67 for ABC-DLBCL, one-sided P = .1. CONCLUSION: In this signal-seeking study, the addition of lenalidomide to R-CHOP (R2CHOP) improved outcomes in newly diagnosed DLBCL including patients with ABC-DLBCL.